Investasi Syariah dan Pertumbuhan Ekonomi: Optimasi Peran Sukuk Sebagai Penunjang Pembangunan Ekonomi Nasional - Reza Henning Wijaya (Jurnal Ekonomi Akuntansi dan Manajemen, 2021)
Massive movement of sharia things in the world, it given impact to all of countries, no exception Indonesia. This descriptive research aims to depict sharia investement especially sukuk able to contribute in national economy development. This research method is qualitative with library research. Sukuk able to cover deficit Indonesia APBN to support infrastructure developing, built labor insentive, and developing region potency. But Indonesia still needs some regulations and policies to optimize role of sukuk in national economy development itself. Keywords: Sukuk, National Economy Development, APBN.